LINGUISTIC ANALYSIS OF PHRASEOLOGICAL UNITS WITH FOOD COMPONENTS IN ENGLISH AND UZBEK LANGUAGES - Eshquvvatova Gulasal Abdullo qizi (Galaxy International Interdisciplinary Research Journal, 2023)
The article is devoted to the linguo-cultural analysis of phraseological units in the phraseology of the English and Uzbek languages. According to the results of the analysis, expressions on some topics belong only to the lexicon of a certain people. Among these are phrases expressing geographical location in Uzbek language and related to myths and phrases related to fairy tales in English.